A cidade como tabuleiro : um estudo das dinâmicas de jogo na rede social móvel Foursquare - Reis, Breno Maciel Souza (2013)
This work fits in studies of the phenomenon of play and its occurrence as an essential mediator of formation and sharing of symbolic forms from human communication, and therefore, the society itself. From the understanding of massive technological devices in everyday life and the overlapping between these ones, the information networks and public space of cities itselves, which now can be understood as cybercities (Lemos, 2004), we studied the elements of gameplay present in the mobile social network Foursquare, as a possible appropriation by its users and its transformation into a locative mobile game. The netnography was used as the methodological bias, mostly from Hine (2000) and Kozinetz (2010), to approach the object; and the concept of ludema, proposed by Pinheiro and Branco (2011, 2012) to the analysis of game mechanics in this social network from the perspective of game studies, and the identification of those at Foursquare - besides being possible to be understood as a playful system governed by specific rules and based on competition among the participants as the driving force of those elements. It also presents, as a complement, the observation of 10 users profiles of the social network, searching for clues that might confirm the use of it as a game, as the accumulation of symbolic goods specific to the system, understood as achievements, and also relations of conflict and competition, understanding the interaction processes essentially as admitted by the mobile network.